1996
DOI: 10.1046/j.1365-2796.1996.484820000.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen dioxide pneumonitis in ice hockey players

Abstract: Exposure to the toxic gases carbon monoxide and nitrogen dioxide (NO2) in indoor ice arenas occasionally occurs and may result in severe symptoms. The gases are produced by ice resurfacing machines operating on hydrocarbons, and in certain conditions toxic levels accumulate. The damage to lung tissues caused by NO2 may not be evident until after a latency time of 1/2-2 days. The role of corticosteroids in the treatment is controversial, but there are clinical experiences as well as experimental data supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 11 publications
0
20
0
Order By: Relevance
“…High concentrations can kill within minutes. Moderate concentrations inhaled for extended periods may produce severe symptoms whose onset can be delayed between 5 and 72 hours (45,46). The clinical syndrome of NOx exposure is more prominently pulmonary than ODTS and characterized by cough and dyspnea, and may also include fatigue, nausea, headache, abdominal pain, and fever.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…High concentrations can kill within minutes. Moderate concentrations inhaled for extended periods may produce severe symptoms whose onset can be delayed between 5 and 72 hours (45,46). The clinical syndrome of NOx exposure is more prominently pulmonary than ODTS and characterized by cough and dyspnea, and may also include fatigue, nausea, headache, abdominal pain, and fever.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…Outbreaks of respiratory illness have been reported after exposure to very high concentrations of NO 2 in ice arenas, i.e. in the order of several thousands of mg?m -3 , probably due to malfunctioning of combustion engines and poor ventilation [7,8]. In follow-up investigations after such accidents no long-term health effects have been demonstrated [7,8].…”
mentioning
confidence: 99%
“…in the order of several thousands of mg?m -3 , probably due to malfunctioning of combustion engines and poor ventilation [7,8]. In follow-up investigations after such accidents no long-term health effects have been demonstrated [7,8]. However, there is a lack of studies on long-term effects of regular exposure to high NO 2 concentrations in ice arenas.…”
mentioning
confidence: 99%
“…Hedbery et al 4 found 89% of the young hockey players with asthma reported more severe symptoms after exposure. In other cases, Morgan 7 and Karlson-Stilber et al 23 have documented pulmonary oedema in young hockey players after exposure to low concentrations of NO 2 during a hockey game. In these incidents, a malfunctioning ice resurfacer was the source of NO 2 , and high concentrations remained in these rinks due to inadequate ventilation systems.…”
Section: Contaminantsmentioning
confidence: 96%
“…There has been only one study which investigated particulates 30 and one involving volatile organic compounds. 23 These chemicals are very serious toxins. Even in isolation these irritants have the potential to be a serious health hazard, but in combination they may pose an even greater potential for adverse health effects.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%